Eksperimen Isolasi DNA Sederhana Berbasis STEAM Dalam Meningkatkan Keterampilan Interdisipliner - Lauda Feroniasanti, Yoanni Maria; Murwaningtyas, Chatarina Enny; Novella Krisnamurti, Cyrenia; Sri Pratini, Haniek; Yuli Listyarini, Ika (Wisanggeni: Jurnal Pengabdian Masyarakat, 2025)
Genetic material is often considered difficult because it is abstract and difficult to visualize. One topic in genetic material is DNA isolation. DNA isolation practicums are rarely conducted in schools because many teachers consider DNA isolation requires complicated equipment and is expensive. This simple DNA isolation experiment is one topic that can be studied using a STEAM-based approach. Stella Duce Bambanglipuro High School has the equipment to support simple DNA isolation experiments using local fruits available in the area. This community service activity aims to introduce learning activities using the STEAM approach for simple fruit DNA experiments using papaya and pineapple. The method used in the community service is Asset-Based Community Development (ABCD). The ABCD method was chosen as the approach in this community service activity because it emphasizes the utilization of local assets and potential of the school. Based on the results of the activity, it shows that the STEAM approach based on simple experiments is effective in increasing engagement and interest in learning science among students at Stella Duce Bambanglipuro High School, Bantul. This program successfully connects scientific theory with contextual practice, strengthens interdisciplinary collaboration, and provides a fun learning experience